Misclassification of Hypertension Status According to Office Blood Pressure vs 24-Hour Ambulatory Blood Pressure Monitoring - Gregory L. Hundemer, MD, MPH; Ayub Akbari, MD, MSc; Amos Buh, PhD; Nandini Biyani, BSc; Shaafi Mahbub, BSc; Maria Salman, BSc; Pierre A. Brown, MD; Greg A. Knoll, MD, MSc; Manish M. Sood, MD, MSc; Swapnil Hiremath, MD, MPH; Marcel Ruzicka, MD, PhD (CJC Open)
Background: Ambulatory blood pressure monitoring (ABPM) is the gold standard for establishing the diagnosis of hypertension yet remains underused in Canada. There remains a scarcity of Canadian data surrounding how commonly misclassification of hypertension phenotypes occurs without regular use of ABPM. Methods: This cross-sectional study included 964 consecutive adult patients referred to the Ottawa Hospital Hypertension Clinic who underwent same-day ABPM and automated office-based blood pressure measurement (AOBPM) between 2019 and 2023. The proportion of hypertension status misclassification was determined by comparing ABPM and AOBPM values. White coat hypertension (if on no antihypertensive medication) or white coat effect (if on antihypertensive medication) was defined as AOBPM ≥140/90 mm Hg but mean 24-hour ABPM <130/80 mm Hg. Masked hypertension (if on no antihypertensive medication) or masked uncontrolled hypertension (if on antihypertensive medication) was defined as AOBPM <140/90 mm Hg but mean 24-hour ABPM ≥130/80 mm Hg. Results: The mean (SD) age was 60 (16) years, and 46% of the patients were female. Among 296 patients with normotension or controlled hypertension based on ABPM, 146 (49%) met criteria for white coat hypertension (n = 21) or white coat effect (n = 125). Among 668 patients with uncontrolled hypertension based on ABPM, 364 (54%) met criteria for masked hypertension (n = 65) or masked uncontrolled hypertension (n = 299). Conclusions: The hypertension status of approximately 50% of patients was misclassified by AOBPM vs ABPM. Broader use of ABPM in Canada will improve hypertension awareness, treatment, and control rates. Résumé: Contexte: Le monitorage ambulatoire de la pression artérielle (MAPA) est la référence pour établir le diagnostic d’hypertension, bien qu’il demeure sous-utilisé au Canada. Les données canadiennes sont encore trop limitées pour permettre d’établir la fréquence des erreurs de classification des phénotypes de l’hypertension lorsque le MAPA n’est pas utilisé sur une base régulière. Méthodologie: Cette étude transversale comptait 964 adultes consécutifs orientés vers la clinique de l’hypertension de l’hôpital d’Ottawa qui ont été soumis, le même jour, à un MAPA et à une mesure de la pression artérielle automatisée au cabinet entre 2019 et 2023. Les erreurs sur le statut hypertensif ont été déterminées en comparant les valeurs du MAPA et celles de la mesure de la pression artérielle automatisée au cabinet. L’hypertension de consultation (en l’absence de traitement antihypertenseur) ou l’effet de la blouse blanche (en présence d’un traitement antihypertenseur) étaient définis comme une mesure de la pression artérielle automatisée au cabinet ≥ 140/90 mmHg, mais avec une valeur de MAPA moyenne sur 24 heures < 130/80 mmHg. L’hypertension masquée (en l’absence de traitement antihypertenseur) ou l’hypertension non maîtrisée masquée (en présence de traitement antihypertenseur) étaient définies comme une mesure de la pression artérielle automatisée au cabinet < 140/90 mmHg, mais avec une valeur de MAPA moyenne sur 24 heures ≥ 130/80 mmHg. Résultats: L’âge moyen (écart-type) était de 60 (16) ans; 46 % des patients étaient des femmes. Sur les 296 patients affichant une pression normale ou une hypertension maîtrisée selon le MAPA, 146 (49 %) répondaient aux critères de l’hypertension de consultation (n = 221) ou de l’effet de la blouse blanche (n = 125). Sur les 668 patients présentant une hypertension non maîtrisée selon le MAPA, 364 (54 %) répondaient aux critères d’hypertension masquée (n = 65) ou d’hypertension non maîtrisée masquée (n = 299). Conclusions: Par rapport au MAPA, la mesure de la pression artérielle automatisée au cabinet a faussé l’interprétation du statut hypertensif chez environ 50 % des patients. Une utilisation élargie du MAPA au Canada permettra de mieux connaître l’hypertension, son traitement et son taux de maîtrise.